Characterization of peripheral cannabinoid receptor expression and clinical correlates in schizophrenia. (30th November 2016) - Chase, Kayla A.; Feiner, Benjamin; Rosen, Cherise; Gavin, David P.; Sharma, Rajiv P.
Abstract: The relationship between cannabinoid receptor signaling and psychosis vulnerability requires further exploration. The endocannabinoid signaling system is extensive, with receptors exerting regulatory functions in both immune and central nervous systems. In the brain, cannabinoid receptors (CBR) directly modulate neurotransmitter systems. In the peripheral lymphocyte, CBRs mediate cytokine release, with dysregulated cytokine levels demonstrated in schizophrenia. mRNA levels of CBRs were measured in human peripheral blood mononuclear cells (PBMCs) obtained from 70 participants (35 non-clinical controls, 35 participants with schizophrenia), who were recruited for the absence of marijuana use/abuse by self-report. Changes in mRNA expression were measured using qRT-PCR. Clinical measurements collected included the MATRICS Cognitive Battery and the Positive and Negative Syndrome Scale. Levels of CB1R and CB2R mRNA in PBMCs were significantly higher in participants with schizophrenia compared to the non-clinical controls. Additionally, CB1R and CB2R mRNA levels correlated with impairments in cognitive processing and clinical symptom severity in multiple domains. These results continue to support dysregulation of particular aspects of the endocannabinoid signaling system in participants with schizophrenia selected for the self-reported absence of marijuana abuse/dependence. Highlights: Cannabinoid receptor mRNA levels are elevated in peripheral cells of schizophrenia patients. Elevated cannabinoid receptor levels correlate with cognitive processing impairments and symptom severity. Cannabinoid receptors mediate cytokine release in the peripheral lymphocyte. Cytokine levels are shown to be dysregulated in schizophrenia. Aberrant cannabinoid signaling appears to be a contributing factor to schizophrenia symptoms.